2021
DOI: 10.1021/acsearthspacechem.0c00335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Environmental Film Maturation through a Deliquescence–Efflorescence Model

Abstract: As atmospheric particulate and (semi)volatile molecules gradually deposit on outdoor surfaces, they create heterogeneous coatings known as environmental films. The unique chemical environments within these films will impact local environmental chemistry. We report the effects of water vapor and deliquescence/efflorescence cycling on particles incorporated into these films within three model systems created in our laboratory: pure salt, pure organic, and mixed salt-organic films, ranging from 1 to 5 μm thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…8 Quantifying water affinities for different film chemistries has important implications for stormwater quality and tracking fate and transport of persistent organic pollutant materials entrained within the films. 2,16 In this study, we examine films collected at two sites near Iowa City, Iowa. The two sampling sites are separated by ∼1 km.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Quantifying water affinities for different film chemistries has important implications for stormwater quality and tracking fate and transport of persistent organic pollutant materials entrained within the films. 2,16 In this study, we examine films collected at two sites near Iowa City, Iowa. The two sampling sites are separated by ∼1 km.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Baergen et al have shown a surprising trend of higher water uptake of films collected in the summer in comparison to their winter counterparts and rationalized this suggesting an unidentified species controlling water uptake . Quantifying water affinities for different film chemistries has important implications for stormwater quality and tracking fate and transport of persistent organic pollutant materials entrained within the films. , …”
Section: Introductionmentioning
confidence: 99%